PENGARUH SENAM DIABETIK TERHADAP PENURUNAN KADAR GULA DARAH PADA LANSIA DI WILAYAH KERJA PUSKESMAS TEBON DI DESA BOGOREJO KECAMATAN BARAT KABUPATEN MAGETAN - Kusyani, Asri; Aziz, Aditya Nuraminuddin; Amiatun, Ambar (WELL BEING, 2020)
Diabetes mellitus is a chronic, progressive disease that is characterized by the bodyʼs inability to metabolize carbohydrates, fats, and proteins early in the occurrence of hyperglycemia (high sugar levels in the blood). The purpose of this study was to determine the effect of diabetic gymnastics on reducing blood sugar levels before and after diabetes gymnastics in Tebon Puekesma areas in Bogorejo Village, Barat District of Magetan Regency. The research method used was pre-experimental (one-group-pre-post test design). The number of samples collected 63 elderly respondents aged 46- 69 years with the inclusion criteria of 20 elderly respondents with high sugar levels. Among the 20 elderly respondents with high sugar levels, there is found 3 normal respondents (15%), 11 respondents with diabetes (55%) and 6 respondents were high (30%). Based on Wilcoxon test results obtained p = 0.000, where p < 0.05 so that H1 is accepted which means there is an influence between blood sugar levels before and after diabetic, gymnastic. In reality, that diabetic gymnastics can reduce blood sugar levels of diabetics, but other factors also influence diabetes mellitus, namely: heredity.